O regime de progressão continuada e as implicações na organização escolar em escolas da Rede Estadual de Ensino do município de Santa Maria/RS - Pereira, Daiana Braga (2006)
The purpose of this study was to analyze, from the teachers speeches, the Regime of Continued Progression, identifying and understanding its implications in the school organization. This educational politics was implanted, from 2001, in public schools from Santa Maria/RS, in order to diminish the reproof and school-leavers rates. Seeing that the Regime of Continued Progression implies in changes in evaluation process, I present a brief comment on the evaluation conceptions, on the ways of evaluating utilized in education, on the changes in the ways of evaluating from the 90s and a description about the operation of this Regime. To accomplish this study, a survey of the schools, which the Regime was implemented, was made. From this survey, in 11 schools, that had/has adopted the Regime, the documents of a school Pedagogic-Political Project and Regiment of school were analyzed, 110 questionnaires with open questions were applied to schoolmistress. After that, structured interviews were done with a pedagogical coordinator from first grades and with two (2) teachers from groups of progression. The choice for this school was due to the number of questionnaires answered and also due to the fact that the school had abandoned the Regime. The pieces of information obtained from textual analysis of school s documents, from application of questionnaires and also realization of interviews are related to, mainly, the changes in school organization after the adoption of the Regime, the evaluative process, the conceptions about this Regime as well about groups of progression from teachers. These pieces of information make evident that the teachers consider the Regime an imposition and, consequently, it caused a strong resistance for it by these professionals. At the same time, some positive changes also happened, for instance, the use of descriptions about the student s behavior and performance and groups of progression. Hence, it was possible to perceive that there was already teachers resistance to this Regime before it had been adopted. The changes caused by the adoption of the Regime increased the resistance to it, because teachers felt themselves without conditions to deal with unknown situations. Furthermore, these changes also involved the teachers conceptions of school, of education, of knowledge and so on. The Regime of Continued Progression brings the possibility for teachers rethink about their practices, reviewing their conceptions.